Share Buybacks Without General Meeting Approval: Ratio Legis and Shareholder Protection - Reynaldi Sepriyan Prayoga; Sudaryat Sudaryat (Magister Hukum Universitas Semarang, 2026)
Financial Services Authority Regulation No. 13 of 2023 permits share buybacks without a General Meeting of Shareholders (GMS) during significantly fluctuating market conditions as a market stabilization instrument. Despite this, prior research has not sufficiently addressed the policy’s implications for corporate governance and legal protection of shareholders, particularly regarding the removal of the GMS requirement. The present study analyzes the ratio legis of the criteria for significant fluctuations in markets and evaluates legal protections for shareholders in share buybacks conducted without a GMS. Employing a juridical-normative method with statutory and conceptual approaches, the findings indicate that the criteria for significantly fluctuating markets lack objective and measurable formulation, resulting in broad discretionary authority. Legal protection mechanisms are primarily formal, relying on information disclosure without substantive shareholder participation, and the application of repressive protection remains limited in practice. These conditions exacerbate information asymmetry and heighten the vulnerability of minority shareholders. The study identifies an imbalance between market stability objectives and shareholder protection and recommends enhanced legal safeguards through an ex post GMS approval mechanism and improved participatory information disclosure. Furthermore, it is advised that the Financial Services Authority (OJK) utilize a Circular Letter containing scientifically reliable economic data and indicators when determining significantly fluctuating market conditions Keywords: Buyback; Capital Market ;Fluctuating Market,;General Meeting of Shareholders.